Bone valley : a true story of injustice and redemption in the heart of Florida - King, Gilbert (Flatiron Books, 2025)
"From Pulitzer Prize-winning author Gilbert King comes a chilling exploration of one of America's most haunting wrongful conviction cases. Based on the hit podcast, Bone Valley dives into the dark heart of rural Florida, where a young man's life was upended by a tragic miscarriage of justice. In 1987, Leo Schofield was arrested and charged with the murder of his wife, Michelle. Always insistent on his innocence, he was poorly served by his legal defense: the investigation was sloppy, the case flimsy, and numerous pieces of evidence were ignored. He was sentenced to life in prison. Over thirty years later, Gilbert King is tipped off to Leo's case and is astonished by what he found: layers of corruption, flawed evidence, and deep-seated errors. He can't shake the story and starts to get to know Leo and his family. Leo shows an incomprehensible amount of grace and love about his situation, which spurs Gilbert even more to tell his story. Bone Valley is at once a revelatory investigation into a murder, a chilling portrait of the criminal justice system, and a uniquely powerful story of grace and redemption. Gilbert King has written a new classic of narrative nonfiction"-- Provided by publisher.